National Economic Burden Associated with Management of Periodontitis in Malaysia - Tuti Ningseh Mohd Dom; Rasidah Ayob; Khairiyah Abd Muttalib; Syed Mohamed Aljunid (International Journal of Dentistry)
Objectives. The aim of this study is to estimate the economic burden associated with the management of periodontitis in Malaysia from the societal perspective. Methods. We estimated the economic burden of periodontitis by combining the disease prevalence with its treatment costs. We estimated treatment costs (with 2012 value of Malaysian Ringgit) using the cost-of-illness approach and included both direct and indirect costs. We used the National Oral Health Survey for Adults (2010) data to estimate the prevalence of periodontitis and 2010 national census data to estimate the adult population at risk for periodontitis. Results. The economic burden of managing all cases of periodontitis at the national level from the societal perspective was approximately MYR 32.5 billion, accounting for 3.83% of the 2012 Gross Domestic Product of the country. It would cost the nation MYR 18.3 billion to treat patients with moderate periodontitis and MYR 13.7 billion to treat patients with severe periodontitis. Conclusion. The economic burden of periodontitis in Malaysia is substantial and comparable with that of other chronic diseases in the country. This is attributable to its high prevalence and high cost of treatment. Judicious application of promotive, preventive, and curative approaches to periodontitis management is decidedly warranted.